SARS-CoV-2 seroprevalence in oncology healthcare professionals and patients with cancer at a tertiary care centre during the COVID-19 pandemic. Issue 5 (2nd September 2020) - Fuereder, Thorsten; Berghoff, Anna Sophie; Heller, Gerwin; Haslacher, Helmuth; Perkmann, Thomas; Strassl, Robert; Berger, Julia Maria; Puhr, Hannah Christina; Kreminger, Judith; Moik, Florian; Schubert, Lorenz; Starzer, Angelika Martina; et al.
Abstract : Background: During the COVID-19 outbreak, healthcare professionals (HCP) are at the frontline of clinical management and at increased risk for infection. The SARS-CoV-2 seroprevalence of oncological HCP and their patients has significant implications for oncological care. Methods: HCP and patients with cancer at the Division of Oncology, Medical University of Vienna were included between 21 March and 4 June and tested for total antibodies against SARS-CoV-2 employing the Roche Elecsys Anti-SARS-CoV-2 immunoassay. Reactive samples were confirmed or disproved by the Abbott SARS-CoV-2 IgG test. Additionally, a structured questionnaire regarding basic demographic parameters, travel history and COVID-19-associated symptoms had to be completed by HCP. Results: 146 subjects (62 HCP and 84 patients with cancer) were enrolled. In the oncological HCP cohort, 20 (32.3%) subjects were medical oncologists, 28 (45.2%) nurses at our ward and 14 (22.6%) fulfil other functions such as study coordinators. In the patient cohort, most individuals are on active anticancer treatment (96.4%). 26% of the HCP and 6% of the patients had symptoms potentially associated with COVID-19 since the end of February 2020. However, only in 2 (3.2%) HCP and in 3 (3.6%) patients, anti-SARS-Cov-2 total antibodies were detected. The second assay for anti-SARS-Cov-2 IgG antibodies confirmed the positive result in all HCP and in 2 (2.4%) patients, suggesting an initial assay's unspecific reaction in one case. In individuals with a confirmed test result, an active COVID-19 infection was documented by a positive SARS-CoV-2 RNA PCR test. Conclusion: Specific anti-SARS-CoV-2 antibodies were found solely in persons after a documented SARS-CoV-2 viral infection, thus supporting the test methods' high sensitivity and specificity. The low prevalence of anti-SARS-CoV-2 antibodies in our cohorts indicates a lack of immunity against SARS-CoV-2. It highlights the need for continued strict safety measures to prevent uncontrolled viral spread among oncological HCPs and patients with cancer.